Fire resistance and thermal performance of sustainable hybrid carbon/flax fibre reinforced aluminium laminates with silicon carbide filler for aircraft engine fire-designated zones - Balakrishnan, Thinesh Sharma; Saadon, Syamimi; Shen, Yeoh Thian; Nayak, Suhas Yeshwant; Mazlan, Norkhairunnisa (Taylor and Francis, 2025)
This study evaluates the effects of incorporating flax fibers and silicon carbide (SiC) nanoparticles in carbon/aluminum fiber metal laminates, addressing a critical research gap in sustainable, fireproof composites for aerospace fire-designated zones. Unlike previous studies that examined plant fiber or SiC-filled composites separately, this work investigates their combined impact within fiber metal laminates under ISO 2685 fire conditions. Four laminate variants, CARALL, CARALL + SiC, CFFRAL, and CFFRAL + SiC were fabricated and tested using fire exposure, Thermogravimetric Analysis (TGA), Dynamic Mechanical Analysis (DMA). All the laminates were classified as fireproof, enduring 1100°C for 15 minutes. TGA showed marginally higher weight loss (~2%) in CFFRAL, while SiC addition increased thermal conductivity by 6.5% in CFFRAL and 6.75% in CARALL, reducing fire insulation. DMA revealed enhanced stiffness in SiC-reinforced laminates, with CARALL + SiC showing the highest storage modulus (10.23 GPa at 30 °C). FESEM analysis confirmed resin burnout in CARALL but improved char retention and ceramic residue in SiC-reinforced laminates, while CFFRAL variants displayed microcracks, voids, and bio-char formation. These findings demonstrate the viability of flax fibers in aerospace-grade composites, highlight biochar’s role in sustainability, and emphasize the need to optimize SiC content for balanced mechanical and thermal performance.